Using Land Resources in Agriculture of Belgorod Oblast - Strokov, Anton Sergeevich; Makarov, Oleg Anatolevich; Svetlov, Nikolay Mikhaylovich; Loginova, Darya Aleksandrovna (Economy of Regions, 2019)
In the study, we assess the land resources as an input in agriculture. The research’s novelty is in defining a new role of the land resources’ quality in modern scientific developments at the interface of economics, soil science and ecology. This allows studying the economic consequences of the land mismanagement or soil degradation. Historically, economic analysis has unfairly dropped the studies of the land resources’ quality in the second half of XIX century, focusing on the returnsfrom other factors of production. However, recently a scientific trend has emerged that aims to study the interactions between the land resources’ quality and the economy in general and its branches (especially agriculture) in particular. We applied the obtained methodological findings in the agro-economic research of the degradation of lands in Belgorod oblast. We hypothesised that the soil degradation negatively affects not only the volumes of crop production, but also the total farms’ revenues from all kinds of activities. For assessing the parameters, we used three different variants of the linear and logarithm production function, considering various sets of data. The first variant was in absolute terms. The second and third variants were dependent and independent variables normalised to the area of agricultural land and the capital, respectively. In every case, the soil erosion indicator negatively affected the revenue. The indicator was statistically meaningful with the elasticity less than 1. It means that 1 % growth of the eroded agricultural land in Belgorod oblast leads to 0.3 % decrease of agricultural revenues. At the same time, the revenue’s elasticity per area of agricultural land is only 0.2, meaning that the land resources’ quality plays a more important role than the land area.